2018
DOI: 10.15171/ijtmgh.2018.23
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice among Egyptian Travelers: Pre-travel Vaccination and Malaria Prophylaxis

Abstract: Introduction: More than one third of travelers to developing countries report health problems when traveling. The Egyptian Ministry of Health reports the occurrence of 400 cases of malarial infection yearly among Egyptian travelers. This article aimed to assess the knowledge, attitude, and practice (KAP) of Egyptian travelers towards infectious diseases, vaccination, and malaria chemoprophylaxis. Methods: A survey was conducted at Cairo International Airport and included 1500 travelers. The questionnaire inqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
3
4
0
Order By: Relevance
“…Logistic regression analysis found that low education was significant predictor for more unsatisfactory knowledge, and poor practice which concedes with other KAP studies [ 39 ]. Insufficient income was a predictor for more negative attitude which agrees with previous studies [ 36 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…Logistic regression analysis found that low education was significant predictor for more unsatisfactory knowledge, and poor practice which concedes with other KAP studies [ 39 ]. Insufficient income was a predictor for more negative attitude which agrees with previous studies [ 36 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…Model I illustrates a noteworthy association between younger age and knowledge of travel-related infectious diseases. This finding aligns with a previous study conducted among Chinese travelers [44] but contradicts the results of studies conducted among Arabian [45] and Egyptian [41] travelers. These differences might be the result of socio-cultural disparities, where variations in education, healthcare access, and cultural norms regarding travel and health can substantially impact knowledge levels concerning travel-related infectious diseases.…”
Section: Discussionsupporting
confidence: 76%
“…Several studies in the literature have investigated knowledge, attitudes, and behaviors towards travel-related infectious diseases; however, these studies mainly focus on specific populations, such as international travelers or frequent flyers, or on a specific travel-related infectious disease [27,28,[35][36][37][38][39][40][41][42][43][44][45][46][47][48]. The literature highlights the significant need for education, as travelers often lack awareness of potential health hazards and fail to take essential precautions, such as getting vaccinated or seeking medical advice prior to their travels.…”
Section: Introductionmentioning
confidence: 99%
“…The number of people traveling internationally has continued to grow substantially in the past decade [2]. Vaccines are one of the most cost effective and successful approaches to protecting individuals from a wide range of diseases, and have resulted in the prevention ofhundreds of thousands of deaths and millions of hospitalizations in the United States and worldwide [1].…”
Section: Introductionmentioning
confidence: 99%
“…Recent outbreaks of vaccine-preventable diseases such as measles and mumps in the United States have been traced to contact with persons who had traveled to locations where vaccination was more prevalent. In addition, travel and migration have contributed to the recent introduction or reintroduction of vector-borne diseases in places that had previously been free from these diseases [2].…”
Section: Introductionmentioning
confidence: 99%